'Strong, United and Independent': the British Foreign Office, Anglo–Iranian Oil Company and the internationalization of Iranian politics at the dawn of the Cold War, 1945–46. Issue 3 (3rd May 2016) - Shaw, Alexander Nicholas
ABSTRACT: This article challenges traditional accounts of the 1946 Cold War Crisis in Iran by moving beyond Soviet–American confrontation to focus on British policy. In contrast to the United States, Britain was a major stake-holding power in Iran due to the valuable holdings of the Anglo–Iranian Oil Company (AIOC). By comparing the reactions of the AIOC and Foreign Office, continuity between the events of the 1946 Crisis and later developments in the Mosaddegh premiership becomes apparent. Soviet interference in Azerbaijan prompted great concern from representatives in Iran, but the central Foreign Office pursued a more cautious policy. Only concerns relating to the growth of domestic Iranian communism in the form of the Tudeh Party and the threat this entailed to the British concession prompted the Foreign Office and AIOC to take measures rendering them partially complicit in the internationalization of Iranian politics, setting an important precedent for future action. This article evaluates the policy-making process and its impact on Anglo–Iranian relations by utilizing records from the UK National Archives, British Petroleum Archive and diplomatic personal papers.